2020
DOI: 10.1126/sciadv.aax6999
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of Hsp90-induced oligomerizaton of Tau

Abstract: Aggregation of the microtubule-associated protein Tau is a hallmark of Alzheimer's disease with Tau oligomers suspected as the most toxic agent. Tau is a client of the molecular chaperone Hsp90, although it is unclear whether and how the chaperone massages the structure of intrinsically disordered Tau. Using electron paramagnetic resonance, we extract structural information from the very broad conformational ensemble of Tau: Tau in solution is highly dynamic and polymorphic, although "paper clip"-shaped by lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 65 publications
(99 reference statements)
0
38
1
Order By: Relevance
“…Moreover, HSPs and protein disaggregases are also implicated in combating protein misfolding and aberrant protein aggregation [ 57 , 58 ]. HSPs (e.g., Hsp70 and Hsp90) are important inhibitors of protein aggregation by protecting the exposed hydrophobic regions from aggregation [ 59 , 60 , 61 ]. Yeast Hsp104 can reverse toxic aggregates formed by α-synuclein, tau, Aβ, PrP and amylin [ 62 , 63 ], thus reducing the toxic species and restoring native function to proteins sequestered within aggregates [ 59 ].…”
Section: Regulation Of Functional Amyloid-like Aggregate Formationmentioning
confidence: 99%
“…Moreover, HSPs and protein disaggregases are also implicated in combating protein misfolding and aberrant protein aggregation [ 57 , 58 ]. HSPs (e.g., Hsp70 and Hsp90) are important inhibitors of protein aggregation by protecting the exposed hydrophobic regions from aggregation [ 59 , 60 , 61 ]. Yeast Hsp104 can reverse toxic aggregates formed by α-synuclein, tau, Aβ, PrP and amylin [ 62 , 63 ], thus reducing the toxic species and restoring native function to proteins sequestered within aggregates [ 59 ].…”
Section: Regulation Of Functional Amyloid-like Aggregate Formationmentioning
confidence: 99%
“…Although Hsp90 is normally thought to act as cellular protection during stress, Hsp90 binding to tau at the VQIVYK motif facilitates a conformational change that results in its phosphorylation by glycogen synthase kinase 3, which further promotes tau aggregation [ 28 ]. Additionally, a recent study found that Hsp90 binding to tau uncovered the repeat domains by conformationally opening the ‘paper-clip’ structure of tau, suggesting that the formation of tau oligomers was caused by the conversion of tau monomers from inert to aggregation-prone forms [ 29 ].…”
Section: Factors Involved In the Formation Of Tau Seedsmentioning
confidence: 99%
“…In line with this, HSPB1 overexpression decreased Tau levels and rescued the Tau mediated damage in a mouse model (Abisambra et al, 2010 ). Interestingly, HSP90 stabilizes aggregation-prone conformations of Tau and promotes oligomer formation in vitro (Weickert et al, 2020 ). However, the fate of Tau is highly dependent on the specific HSP90 co-chaperone (Shelton et al, 2017 ).…”
Section: The Role Of Chaperones In Prion-like Propagationmentioning
confidence: 99%